The Humanisation of Lithuanian Economy as the Precondition of its Effective Integration into European Community - Vasiljevienė, Nijolė (Ekonomika, 2003)
The process of Lithuanian integration into everbroadening EC structures requires not only principal reorientation of its economics but also radical changes of economic relations. The article covers the aspects of business ethics institutionalisation in companies and society relating them to the concepts of sustainable development, stakeholder, “3-c”, “triple bottom line” that have modified modern management strategies and formed attributes of “new economics” and “humanisation of economics”.Today in most dcvc:loped countries of EC the new social ethical paradigms are incorporated into modem strategies of economy. The humanistic attitudes are inherent to strategies of sustainable development and appropriate economics ecological and social parameters of progress that arc in equilibrium and harmony. To ensure a company’s longevity, its successful long-term operation the workplace environment must be improved and humanized. For this purpose ethics tools can be successfully used. They are necessary to survive under the condition of socially oriented economy, which is becoming prevalent in the EU.The purposeful humanization of economics is being successfully conducted through the process of business ethics institutionalization in organizations and assures real benefit’i to the society. So laws, standards, ethics codes frame order; it becomes the basement to achieve valuable life, and ethics codes and standards - instruments to reach these goals. With regard to Lithuania it is very important to emphasize that not only legal but also ethical regulations are critically needed to “switch on” the appropriate mechanism to establish order in organizations. Ethics infrastructure of a company paves the way for self-regulation. In advanced practice of developed countries the company’s activity is developed in accordance with ethical requirements that arc implemented by the appropriate company’s ethics infrastructure and by outside ethics mechanisms. These mechanisms arc functioning in the context of human rights set at the legal and moral level in various fields of life (the employee’s, the consumer’s, the patient’s human rights, etc.) in democratic societies. Certain common tendencies typical of modern society can be traced in the practice of developed countries: when administrative and legal norms and sanctions are not effective, ethics tools are instrumentally applied as follows: inside the company they constitute procedures aimed at the development of ethics infrastructure (programs of ethical training, an ethics code, an ethics board / commission or ethics officer, a hot line, an ethics handbook, etc.)The ethics tools improve the quality of social capital, and human resource management, enable more perfect social order. Practically the point of departure in establishing ethics standards initially brings to implementation of ethical minimum, i.e. the standards of social responsibility termed as the bottom line, and nowadays extended to concept of triple bottom line. The latter constitutes three-dimensional basis consisting of the 3 E - Effectiveness, Ecology, Ethics or 3 P - Profit, People, Planet employed in assessment of companies and organizations. Only the ones, which meet these criteria, are considered trustworthy and prestigious. Meeting labour standards means not only compliance with legal norms but also legitimisation of ethical ones. These standards not only provide the employees with good working conditions but also ensure actualisation of human dignity, justice and safety. These arc issues of life quality, which arc not accentuated in company activity. Therefore, it is very important that every company manager should realize the advantages of responsible behaviour. For this, not only development of a businessperson’s moral attitudes or comprehension that subjective opinions cannot be relied upon is needed; theoretical knowledge, special education is also required. In the world practice ethics criteria, especially that of business arc objectivized and SA 8000 international standard or ILO regulations evidence it. Employees’ rights and conditions that improve workplace environment can be established while implementing social standards or an ethics code. Such regulation of relations between the company and the employees would grant the employees with greater liberties and guarantees as well as form versatile commitments among the company, the employees and the managers. From economic point of view, this is related to growing efficiency, effectiveness and performance quality.With regard to the context of Lithuania’s integration into the European Union, the paper tackles actual issues for associations of Lithuanian trade and industry as well as certain companies, which still dare to disregard the new challenges of this epoch. This means that they do not manage risk and consequently doom themselves to potential scandals, losses of partners, markets, investments, profits, etc.In Lithuania like in some other post communist countries such improvement of social life is impeded only by the lack of economic resources, but also by acute lack of innovative management knowledge provided by business ethics along with old stereotypes and attitudes of mentality. Many facts of Lithuanian reality show what the consequences of exceptionally profit orientation are and witnesses a considerable lack of societal orientation in business and professional activity or ignorance of this actual issue. In turn, absence of business subject’s responsibility to the society can be also traced back to the soviet, nomenclature-based management tradition in which only the privileged persons were entitled to solving inner issues of the business subject’s management.In such relations there arc no equal partnership properties between employers and employees, and their contract is not considered in a wider sense, i.e. as a social contract. The authoritarian management methods inherited by most Lithuanian companies from the soviet period formed such an approach. Thus the need for workplace monitoring and workplace ethics promotion has objectively matured in our country. In Lithuania not many companies really try to improve the workplace conditions promoting appropriate values (human rights related to human dignity, safety, self-esteem, self-realization possibilities).Mature civic societies have managed to prove that economic structures generate social problems and therefore they have to assume responsibility for the consequences of their activity. Democratisation and decentralisation also imply that not the state but the very companies that determine social problems solve them in response to the expectations of citizens (customers). This is the only way they can gain a good name, reputation, and, in turn, increase of sales and consumption, i.e. profit and ability to compete. Therefore, business assumes functions that have never been characteristic to it, e.g. commitment to creation of social well being (first of all inside, then outside) for stakeholders. These are the presuppositions for social contract, compliance with which is monitored or, specifically, self-monitored by social actors.Thus humanization of economics through the development and application ethical infrastructure to the practice of enterprises under the conditions of modern Lithuania is strategically important for its sustainable economic, social development and is the vital precondition of its effective integration into European community.